The Definition of the traffic accident and concept in KSA - Ali, Abdul-Magid Rashed (Journal of Economic, Administrative and Legal Sciences, 2021)
The current research aims to explain the most important causes of traffic accidents in the Kingdom of Saudi Arabia, to identify the effect of modifications to the traffic system in reducing these accidents, as well as to identify the most common types of traffic accidents and ways to reduce their occurrence in the Kingdom of Saudi Arabia, and the researcher used to achieve the research objectives the theoretical approach Analytical reference to traffic accidents statistics and their analysis, and the research has resulted in several results, the most important of which is that modifications to the traffic system contribute to reducing traffic accidents, and it is important to study the obstacles that exist within the right of way and main streets, and pay attention to providing lighting, that most of the drivers ’mistakes causing death are considered violations of regulations Traffic, and the most common disadvantages of vehicles involved in traffic accidents are the invalid paths, and that the majority of pedestrians injured in traffic accidents were their behavior during the accident on walking on the road and not in the place designated for walking.Accordingly, the researcher recommended several important recommendations, including the necessity of taking deterrent measures against the perpetrators of traffic violations, especially excessive speeding, cutting the red signal and overtaking from the right, as well as digging into the ground with car tires, and it also requires the need to address the problem of loose camels and the problems of rainwater and flood drainage. And the need to provide traffic monitoring cameras at all signals, especially those with frequent accidents, and to encourage research and studies on violations and traffic accidents and to take their findings and recommendations into account.
Keywords: traffic accidents; traffic regulation law; drifting